2013
DOI: 10.1002/jhm.2057
|View full text |Cite
|
Sign up to set email alerts
|

FUTURE: New strategies for hospitalists to overcome challenges in teaching on today's wards

Abstract: Changes in the clinical learning environment under resident duty hours restrictions have introduced a number of challenges on today's wards. Additionally, the current group of medical trainees is largely represented by the Millennial Generation, a generation characterized by an affinity for technology, interaction, and group‐based learning. Special attention must be paid to take into account the learning needs of a generation that has only ever known life with duty hours. A mnemonic for strategies to augment t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
24
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 23 publications
2
24
0
1
Order By: Relevance
“…Previous study showed that a flipped classroom based on an automated tutoring system had subsequent issues with grasping of concepts (Strayer et al, 2012). In another study (Martin et al, 2013) it was concluded that a flipped classroom using applications to highlight teaching points had no difference in effectiveness from a conventional classroom teaching. However, there have been few studies appraising the practicability of the medical students to the flipped classroom learning.…”
Section: Introductionmentioning
confidence: 98%
“…Previous study showed that a flipped classroom based on an automated tutoring system had subsequent issues with grasping of concepts (Strayer et al, 2012). In another study (Martin et al, 2013) it was concluded that a flipped classroom using applications to highlight teaching points had no difference in effectiveness from a conventional classroom teaching. However, there have been few studies appraising the practicability of the medical students to the flipped classroom learning.…”
Section: Introductionmentioning
confidence: 98%
“…Most residents use a smartphone, 4 and educators have recognized that using smartphone applications as a teaching tool 5 can increase efficiency in an environment limited by time constraints. 6,7 The high prevalence of text messaging by residents has created an opportunity for a new approach to resident education. 8 Some programs have reported on using text messages to successfully communicate with their residents, including a surgical residency program that implemented a system for residents to report their duty hours, and they found this approach effective, as residents were comfortable using text messages to communicate with program leadership.…”
Section: Introductionmentioning
confidence: 99%
“…Medical educators in the clinical environment have proposed instructional strategies they believe align teaching with today’s millennial learner preferences [13]. Of the variety suggested, from ‘flipping the wards,’ to ‘embedding teaching moments into rounds,’ few capitalize on strategies related to motivation, particularly of the type suggested by self-determination theory.…”
mentioning
confidence: 99%